La discriminación salarial a la población indígena de la provincia de Bolívar y sus efectos en el mercado laboral. - Hidalgo Silverio, Marjorie Lisseth (My University, 2019)
In this investigation the existence of wage discrimination towards the indigenous population of the province of Bolívar was determined. In Ecuador, as in other Andean countries, the ethnographic and cultural composition is diverse, presenting diverse population groups such as mestizos, indigenous, Afro-descendants, etc. It is observed that some groups have better economic and social conditions than others, this situation has generated different dynamics of development for people belonging to different groups. These differences are evident in our days, especially in the indigenous population, which has a socioeconomic situation in more precarious conditions than mestizo people and those considered white. The objective of the research is: To analyze wage discrimination in the indigenous population of the province of Bolivar to recognize its effects on the labor market. The specific objectives are: Define wage discrimination; identify the most vulnerable groups in the labor market in the province of Bolívar, determine the effects of wage discrimination. The results obtained in the investigation show that in the province of Bolívar the wage discrimination is lower than that experienced in the rest of the country. A large part of this population group is engaged in activities such as agriculture, mining and quarrying, transport and commerce, usually the informal one.
En esta investigación se determinó la existencia de la discriminación salarial hacia la población indígena de la provincia de Bolívar. En el Ecuador, al igual que en otros países andinos, la composición etnográfica y cultural es diversa, presentándose grupos poblacionales diversos como mestizos, indígenas, afrodescendientes, etc. Se observa que hay unos grupos poseen mejores condiciones económicas y sociales que otros, esta situación ha generado dinámicas distintas de desarrollo para las personas pertenecientes a los distintos grupos. Estas diferencias son evidentes en nuestros días, especialmente en la población indígena, que posee una situación socioeconómica en condiciones más precarias que las personas mestizas y las consideradas como blancas. El objetivo de la investigación es: Analizar la discriminación salarial en la población indígena de la provincia de Bolívar para reconocer sus efectos en el mercado laboral. Los objetivos específicos son: Definir la discriminación salarial; identificar los grupos más vulnerados en el mercado laboral de la provincia de Bolívar, determinar los efectos de la discriminación salarial. Los resultados obtenidos en la investigación demuestran que en la provincia de Bolívar la discriminación salarial es menor de la que se vive en el resto del país. Gran parte de este grupo poblacional se dedica a actividades como la agricultura, la explotación de minas y canteras, transporte y comercio, generalmente el informal.
Keywords: DISCRIMINACIÓN; SALARIO; MERCADO LABORAL; ETNIA; DIVERSIDAD